China in World and Regional Politics: History and Modernity - Krivorotov, Andrey K.
Since 2019, the U.S. Administration has included the Arctic into its overall China containment policy. Iceland and Greenland attract its special attention as traditional U.S. allies, which play key roles for the control over NATO’s vital maritime communications in North Atlantic, but which have lately developed vibrant contacts with PRC. Greenland has been on the radar in Washington since World War II, regarded within the framework of the Monroe Doctrine, which, although voided officially, still influences the American foreign policy thinking. Now this approach is reinforced by the growing U.S. activities in the Arctic at large and by the global confrontation with Beijing. The key current interests of the United States in Greenland include the security of the strategically important Thule Air Base, preventing large Chinese investments, which would involve the island into the Polar Silk Road initiative, and a potential extraction of rare earth elements. Since mid-2019, the U.S. have launched several major initiatives related to Greenland, the most famous one is President Trump’s offer to purchase it from Denmark. While China focuses on large scale mining projects which Greenland needs to obtain economic independence, and people-to-people contacts, the U.S. concentrate on public policy measures indicating a clear desire to put Greenland under a tighter American control bypassing Copenhagen. Denmark, although a close NATO ally of the United States, is concerned by the activities of both great powers and tries to become a good patron for Greenland to prevent its secession. Meanwhile, the Greenlandic authorities confirm their intentions to struggle for a full-fledged statehood, reflecting the moods of 2/3 of the population. The article suggests three medium-term scenarios, with Greenland remaining in a gradually looser union with Denmark, moving into the U.S. domain or acquiring independence and thus becoming subject to a hard international competition. The next few years may be of special importance for further development, which will also affect Russia as the biggest Arctic nation.